Profesor Holland - Herek, Stephen (Madrid Twentieth Century Fox Home Entertainment España, 2002)
A frustrated composer finds fulfillment as a high school music teacher
Audio : Castellano e inglés. subt.: Castellano e inglés
Writer: Patrick Sheane Duncan
Richard Dreyfuss, Glenne Headly, Jay Thomas
Apta para todos los públicos
Keywords: Películas cinematográficas -- DVD